2013
DOI: 10.1002/bdrb.21063
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Alters Proliferation and Differentiation of Normal and Chromosomally Abnormal Human Embryonic Stem Cell‐Derived Neurospheres

Abstract: Ethanol is a powerful substance and, when consumed during pregnancy, has significant psychoactive and developmental effects on the developing fetus. These abnormalities include growth retardation, neurological deficits, and behavioral and cognitive deficiencies, commonly referred to as fetal alcohol spectrum disorder. The effect of ethanol has been reported to affect cellular development on the embryonic level, however, not much is known about mutations contributing to the influence of ethanol. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Furthermore, we have identified landscapes of molecular networks that are potentially deregulated by EtOH exposure through DNA methylomic alterations. This is in contrast to the recently reported lack of methylation changes after exposure of hESCs to 20 mM EtOH (Krishnamoorthy et al, 2013). Interestingly, their reported selective gene subsets are, for the most part, also unchanged in our study, whereas the much larger set of genes which do show methylation changes in our study are not reported by these authors.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we have identified landscapes of molecular networks that are potentially deregulated by EtOH exposure through DNA methylomic alterations. This is in contrast to the recently reported lack of methylation changes after exposure of hESCs to 20 mM EtOH (Krishnamoorthy et al, 2013). Interestingly, their reported selective gene subsets are, for the most part, also unchanged in our study, whereas the much larger set of genes which do show methylation changes in our study are not reported by these authors.…”
Section: Discussioncontrasting
confidence: 99%
“…Low doses of alcohol have been shown to promote stem cell expansion, while higher concentrations slow proliferation [95,96,97,98,99]. Several cell culture studies indicate that alcohol exposure inhibits neurogenesis [100], while hastening neuronal differentiation [100,101]. During the neurogenic period, alcohol causes a decrease in a variety of neuronal populations including hippocampal CA1 pyramidal cells [102,103,104,105,106,107,108,109,110,111], cerebellar Purkinje cells [112,113,114,115], and cerebral cortical neurons [116,117].…”
Section: Abnormal Differentiation In Fasdmentioning
confidence: 99%
“…These changes may be related to alcohol induction of pro-glutamatergic genes, such as Paired box 6 ( Pax6 ), Neurogenin 2 ( Neurog2 ), and Neurogenic Differentiation-1 ( Neurod1 ) and inhibition of pro-GABAergic Mammalian Achaete Scute Homolog-1 ( Ascl1 ) levels [100]. Additionally, prenatal alcohol exposure alters the distribution and morphology of neurons [101,129]. Ectopic distribution and density of neuronal synapses generated late in gestation have been reported [116,130,131,132,133,134].…”
Section: Abnormal Differentiation In Fasdmentioning
confidence: 99%
“…Accordingly, it is reported that larger colonies of undifferentiated hESC exposed to 20 mM ethanol will increase apoptosis and decreased glial fibrillary acidic protein (GFAP) expression in later differentiation progress, indicating that ethanol reduced astrocyte differentiation potential[ 42 ]. There is also reported that 20 mM ethanol exposure altered the proliferation and differentiation of hESCs-derived neurospheres[ 43 ]. Recently, research showed that 1.0% (0.22M) ethanol exposure could affect the expression of key pluripotency markers in ESC, made the ESCs loss their pluripotency[ 44 ].…”
Section: Resultsmentioning
confidence: 99%